Aonchotheca yannickchavali n. sp. (Nematoda: Capillariidae) in Bandicota indica (Bechstein, 1800) and Bandicota savilei (Thomas, 1916) (Rodentia: Muridae) collected from Thailand - Veciana, Marina; Chaisiri, Kittipong; Morand, Serge; Ribas, Alexis (Agriculture and Natural Resources, 2016)
During previous surveys of helminths in rodents from Southeast Asia, an unnamed species of Aonchotheca was recovered from the stomach of several rodent species. In the present study, the description of the new species Aonchotheca yannickchavali n. sp. is provided based on both female and male specimens collected from two bandicoot rat species (Bandicota indica and Bandicota savilei) from Thailand (Buriram and Nan provinces). This nematode can be separated from other known Aonchotheca found in rodents by its microhabitat in the host and by the size of the spicules in males and the vulvar appendage in females.